Conjugated Polymer Nanoparticle–Graphene Oxide Charge‐Transfer Complexes. (17th April 2018) - Istif, Emin; Hernández‐Ferrer, Javier; Urriolabeitia, Esteban P.; Stergiou, Anastasios; Tagmatarchis, Nikos; Fratta, Giuseppe; Large, Matthew J.; Dalton, Alan B.; Benito, Ana M.; Maser, Wolfgang K.
Abstract: The game‐changing role of graphene oxide (GO) in tuning the excitonic behavior of conjugated polymer nanoparticles is described for the first time. This is demonstrated by using poly(3‐hexylthiophene) (P3HT) as a benchmark conjugated polymer and employing an in situ reprecipitation approach resulting in P3HT nanoparticles (P3HTNPs ) with sizes of 50–100 nm in intimate contact with GO. During the self‐assembly process, GO changes the crystalline packing of P3HT chains in the forming P3HTNPs from H to H/J aggregates exhibiting exciton coupling constants as low as 2 meV, indicating favorable charge separation along the P3HT chains. Concomitantly, π–π interface interactions between the P3HTNPs and GO sheets are established resulting in the creation of P3HTNPs –GO charge‐transfer complexes whose energy bandgaps are lowered by up to 0.5 eV. Moreover, their optoelectronic properties, preestablished in the liquid phase, are retained when processed into thin films from the stable aqueous dispersions, thus eliminating the critical dependency on external processing parameters. These results can be transferred to other types of conjugated polymers. Combined with the possibility of employing water based "green" processing technologies, charge‐transfer complexes of conjugated polymer nanoparticles and GO open new pathways for the fabrication of improved optoelectronic thin film devices. Abstract : Nanoparticles of conjugated polymer poly(3‐hexylthiophene) self‐assembled in the presence of graphene oxide reveal an internal aggregate structure with significantly reduced excitonic coupling constants, which concomitantly favors π–π interactions with graphene oxide sheets toward the formation of a charge‐transfer complex with reduced energy bandgaps and enhanced photoactivity.